The First Life of Bernard of Clairvaux - William, of Saint-Thierry, Abbot of Saint-Thierry, approximately 1085-1148?; Costello, Hilary (Book collections on Project MUSE., 2015)
The First Life of Bernard of Clairvaux, traditionally known as the Vita Prima, originated to prepare the case for canonization of Bernard, first abbot of Cairvaux. The work was begun by William of Saint-Thierry, continued by Arnold of Bonneval, and completed by Geoffrey of Auxerre. When the initial case put forth for Bernard was rejected by Innocent II, Geoffrey undertook a revision of the original vita (Recension A) and submitted another version (Recension B) to Pope Alexander III, who declared Bernard a saint in 1174. This work emphasizes the deep love in which Bernard was held during his life by his monks and the people of France and Italy as well as his role as a powerful public figure. This book contains the first English translation of Recension B, drawn from what is apparently the only manuscript of the work found today in a Cistercian monastery, Mount Saint Bernard Abbey. The introduction begins with the story of how this manuscript came to Mount Saint Bernard, so fixing this translation of the Vita Prima within Cistercian life from the twelfth century to today.